"Dome and Minaret of Sidi Mouaz (552 AH / 1157 AD) Architectural Architectural Study" - Roudah Elbehery (Journal of Architecture, Art & Humanistic Science, 2019)
Abstract One of the first domes in Egypt was the domes of the seven daughters in the year 400 AH / 1010 AD. These seven domes were built individually on each body of the bodies of the seven daughters who were killed by the ruling Caliph after their father fled. The dome is characterized by the existence of an octagonal neck of the dome erected above the tomb with the use of muqarnas in the area of ​​conversion, and from these domes also the dome of Jaafari and Aatek, which dates back to the year 494-514 AH / 1100 - 1120 AD, which is attributed to the Prophet peace be upon him and They each built a mausoleum topped by a dome.  Among these domes is the dome of Mrs. Ruqaya, dating back to 527 AH / 1122 AD, the dome of Sheik Yunus and the dome of the brothers of Joseph, the dome of Yahya al-Shebhi and the dome of Sidi Moaz.    The date of the establishment of this dome was recorded on the foundation plate at the top of the entrance block in the south-eastern facade of the dome, which is 552 AH / 1157 AD.This dome was established by Prince Abu Ghadnafar Asad Al-Fawzi, one of the great princes of the Fatimid state, and one of the emirs of the Fatimid Minister Dhargham. He was attacked against Minister Shawr until Dhargham was appointed by the ministry in 558 AH / 1163 AD. Abu Ghadnafar told him that Prince Abu Ghadnafar and some princes put Prince Dirgham in their hands and that they were the owners of the credit and if they did not support him, then he took over the ministry and then informed him that they had written to the minister to urge him to come to Cairo and promised him help and stand by him until the ministry recovers. They were brought to him at the Ministry House at night and killed them, in early 559 AH / 1163 AD.Abu Ghadnafar built this dome for Sidi Mu'adh bin Dawood al-Hassani in 552 AH / 1157 AD.